UPAYA GURU AL-QUR’AN DALAM MENGATASI KESULITAN BELAJAR MEMBACA AL-QUR’AN DI SDIT UKHUWAH BANJARMASIN - Mubarak, Hafiz (Faculty of Ushuluddin and Humanities, 2013)
This research had goal to gain knowledge about any difficulties experienced by student since learning to read theQuran and what methods used by the Quran teachers to overcome learning difficulties. This research usedqualitative approach. The amount of data source was not determined, but it was based on snowball sampling.Although, the amount of research subject was not determined, the process of moving the research data was onsubjects at SDIT ?Ukhuwah? Banjarmasin. The results showed that the learning difficulties experienced bystudents in the third grade to learn to read the Qur?an were: the students were difficult to concentrate or to focuse;a very active student verbally; slow student learning; student who had a low voice; student shard looked; studentsactively engaged; passive student; students had not been studied together with the child standard abilities; thenumber of children who were too much in the group.